TADAFER II: Tadalafil treatment for fetal growth restriction - a study protocol for a multicenter randomised controlled phase II trial. Issue 10 (30th October 2018) - Umekawa, Takashi; Maki, Shintaro; Kubo, Michiko; Tanaka, Hiroaki; Nii, Masafumi; Tanaka, Kayo; Osato, Kazuhiro; Kamimoto, Yuki; Tamaru, Satoshi; Ogura, Toru; Nishimura, Yuki; Kodera, Mayumi; et al.
Abstract : Introduction: There is no proven therapy to reverse or ameliorate fetal growth restriction (FGR). Sildenafil, a selective phosphodiesterase 5 (PDE5) inhibitor, has been reported to potentially play a therapeutic role in FGR, but this has not been established. Tadalafil is also a selective PDE5 inhibitor. We have demonstrated the efficacy of tadalafil against FGR along with short-term outcomes and the feasibility of tadalafil treatment. Based on the hypothesis that tadalafil will safely increase the likelihood of increased fetal growth in FGR, we designed this phase II study to prospectively evaluate the efficacy and safety of tadalafil against FGR. Methods and analysis: This study is a multicentre, randomised controlled phase II trial. A total of 140 fetuses with FGR will be enrolled from medical centres in Japan. Fetuses will be randomised to receive either the conventional management for FGR or a once-daily treatment with 20 mg of tadalafil along with the conventional management until delivery. The primary endpoint is fetal growth velocity from the first day of the protocol-defined treatment to birth (g/day). To minimise bias in terms of fetal baseline conditions and timing of delivery, a fetal indication for delivery was established in this study. The investigator will evaluate fetal baseline conditions at enrolment and will decide the timing of delivery based on this fetal indication. Infants will be followed up for development until 1.5 years of age. Ethics and dissemination: This study was approved by the Institutional Review Board of Mie University Hospital and each participating institution. Our findings will be widely disseminated through peer-reviewed publications. Trial registration number: UMIN000023778.